PENGEMBANGAN MODEL PEMILIHAN DESAIN PRODUK COOKWARE PROSPEKTIF (Studi Kasus IKM Cor Aluminium di Yogyakarta) - , EKO POERWANTO, Ir. Alva Edy Tontowi, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Various designs cookware products has been launched into the market by various manufacturers, but the growing demand of current cooking activities that spurred the design to more innovative and be able to make cookware to meet the needs of a growing community. There are three objectives in this study: (a) Developing a framework for product design selection model in SMEs cast aluminum, (b) Developing product design selection models with consider to core criteria for product prospective SMEs that can be used on all stakeholders, and (c) Creating design products with specific criteria on cookware prospective at cast aluminum SME that will used on a particular stakeholder. In this research, the MPE and AHP methods used to analyse design product of cookware prospektive.Framework of product design selection of cookware prospective proposed consists of 17 steps, which must be performed by a cast aluminum SMEs stakeholders in the product development program.. Core criteria prospective product design cookware is : Not Easily Scratched (Disability and decay), No Effect on Food (Inert), and Good Heat Transfer (Heat Storage). Specific criteria of prospective cookware products design are Easy to Use and Clean it, Price Affordable (cheap), and the Safe and Convenient for Users (Lid Glass and Ergonomic Handle).